2019
DOI: 10.1088/1742-6596/1280/5/052038
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Laboratory to Improve Pre-service Physics Teachers’ Creativity and Problem-Solving Skills on Thermodynamics Concept

Abstract: Virtual laboratories have been developed in this study as an alternative to the limited equipment of physics experiments. This study aims to examine the effectiveness of virtual lab models to improve creativity and problem-solving skills for prospective physics teachers. The research and development have been divided into 3 phases namely, preliminary study, design development, and model testing. Model testing was performed on two groups of thermodynamic courses using a pre-test post-test control group design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
1
9
0
6
Order By: Relevance
“…The previous results are in line with the results of Gunawan et al. (2019) ; Alneyadi (2019) ; Abou Faour and Ayoubi (2017) ; Pyatt and Sims (2012) who confirmed that VLs increased students’ scientific knowledge, process, and skills and intellectual abilities and attitudes, innovation.…”
Section: Resultssupporting
confidence: 87%
“…The previous results are in line with the results of Gunawan et al. (2019) ; Alneyadi (2019) ; Abou Faour and Ayoubi (2017) ; Pyatt and Sims (2012) who confirmed that VLs increased students’ scientific knowledge, process, and skills and intellectual abilities and attitudes, innovation.…”
Section: Resultssupporting
confidence: 87%
“…In Zhao et al's study [68], a virtual laboratory was designed to support and enrich the undergraduate learners' laboratory experience in addition to the existing physical laboratory; the learners considered that the virtual laboratory was very informative and useful. Studies [69,70] revealed that the use of virtual laboratory media could improve the learners' conceptual understanding, as well as their problem-solving ability [71], and it enhances their creativity [72]. Jiménez et al's study [73] mentioned that virtual laboratories open new learning perspectives that cannot fully be explored in a traditional laboratory.…”
mentioning
confidence: 99%
“…Oleh karena itu, pengembangan berbagai aplikasi pembelajaran semakin banyak dilakukan oleh para praktisi pendidikan (Kusmawan, 2016). Berdasarkan beberapa penelitian sebelumnya, pembelajaran berbasis mobile dirasa cukup efektif dalam meningkatkan keterampilan berpikir (Gunawan et al, 2019). Hal ini dikarenakan dalam sistem mobile learning pembelajaran sarat dengan penggunaan teknologi yang menuntut mahasiswa untuk selalu belajar teknologi (Umar et al, 2020).…”
Section: Pendahuluanunclassified